2018
DOI: 10.1097/sla.0000000000002135
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Occult Intrahepatic Metastasis in Hepatocellular Carcinoma Treated With Transplantation Corresponds to Early Recurrence Rates After Partial Hepatectomy

Abstract: Although the transplant and resection populations differ, occult multifocality is common in transplant explants and similar to the 46% early recurrence rate following partial hepatectomy. These data suggest that noncurative resection often results from occult intrahepatic multifocality present at the time of resection rather than a malignant predisposition of the remnant liver with de novo tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
(12 reference statements)
1
27
0
Order By: Relevance
“…Migration and invasion are the embodiment of tumor metastasis ability. Evidence shows that tumor metastasis occurs at an early stage ( 17 19 ), and suggests that early metastasis is one of the major causes of recurrence and poor prognosis after surgical resection ( 20 ). Moreover, several studies have reported that UTR can stimulate the migration and invasion of many malignant cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Migration and invasion are the embodiment of tumor metastasis ability. Evidence shows that tumor metastasis occurs at an early stage ( 17 19 ), and suggests that early metastasis is one of the major causes of recurrence and poor prognosis after surgical resection ( 20 ). Moreover, several studies have reported that UTR can stimulate the migration and invasion of many malignant cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, we found that expression in TFL was associated with faster and more HCC recurrence as well as worse patient survival after tumor resection. Aufhauser et al (38) hypothesized that early HCC recurrence (< 2 years) after tumor resection in HCC patients is the consequence of occult multi-focality present at the time of tumor resection, but failed to nd markers to identify such occult metastases. The 2-year recurrence rate in our cohort was signi cantly higher in patients with CTA-expression in TFL compared to patients without CTA-expression in TFL.…”
Section: Discussionmentioning
confidence: 99%
“…71 Although increasingly advanced imaging and other techniques are being used to improve detection, as described above, the recurrence of HCC after resection is near 50% in the first few years following resection, mostly likely due to the presence of occult HCC in the remaining liver. 72 In contrast, recurrence after transplantation has been reported to be in the range of 11-18%. 73 Because of the limited supply of deceased donors, or the potential risk to a living donor, it is imperative to minimise recurrence, optimise outcomes, and maximise benefit through careful selection of appropriate recipients.…”
Section: Transplantation For Hccmentioning
confidence: 99%